2021
DOI: 10.1002/cc.20460
|View full text |Cite
|
Sign up to set email alerts
|

A role for disciplinary societies in supporting community college adjunct faculty

Abstract: Disciplinary societies have a role to play in supporting the needs of community college adjunct faculty. The potential exists to improve the professional lives of these faculty members, an underappreciated segment of the higher education workforce, and to positively influence outcomes for students enrolled in community colleges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…The SAGE 2YC: Faculty as Agents of Change project provides a powerful example of the type of PD that taps the potential of adjunct faculty as leaders and agents of change. Efforts to engage and support adjunct faculty, accounting for their needs and experiences, have the potential to “improve the professional lives of these faculty members,” an underappreciated segment of the higher education workforce, and to positively influence outcomes for students enrolled in community colleges (S. Bickerstaff & Ran, 2021, p. 151). This positive influence extends beyond the students in individual classrooms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SAGE 2YC: Faculty as Agents of Change project provides a powerful example of the type of PD that taps the potential of adjunct faculty as leaders and agents of change. Efforts to engage and support adjunct faculty, accounting for their needs and experiences, have the potential to “improve the professional lives of these faculty members,” an underappreciated segment of the higher education workforce, and to positively influence outcomes for students enrolled in community colleges (S. Bickerstaff & Ran, 2021, p. 151). This positive influence extends beyond the students in individual classrooms.…”
Section: Discussionmentioning
confidence: 99%
“…More than two‐thirds of instructional faculty in community colleges are part‐time (Hurlburt & McGarrah, 2016), and more than half of course sections are taught by part‐time faculty (Center for Community College Student Engagement [CCCSE], 2014). Much has been written about issues related to adjunct faculty (e.g., S. E. Bickerstaff & Ran, 2020; S. Bickerstaff & Ran, 2021; Kezar, 2013; Kezar & Sam, 2013, 2014; Leslie & Grappa, 2002; Ortiz et al., 2021). The report on Contingent Commitments: Bringing Part‐Time Faculty into Focus (Center for Community College Student Engagement [CCCSE], 2014) found that many part‐time faculty have limited, unclear, or inconsistent access to “orientation, professional development, administrative and technology support, office space, and accommodations for meetings with students” (p. 3).…”
Section: Introductionmentioning
confidence: 99%
“…Across CUNY 4-year colleges, full-time professors comprise only 45% of the teaching workforce, and at the three colleges sampled, the proportion of annual instructional hours delivered by full-time faculty averages 42% (CUNY Office of Human Resources Management, 2016). Exacerbating part-time faculty members’ capacity to engage first-generation students in the ways that our study participants found helpful are the poor labor conditions that exist for contingent instructors, including low pay, restricted access to faculty resources, and limited availability outside of class due to competing demands, such as teaching a high volume of courses at multiple campuses (Bickerstaff & Chavarin, 2018; Bousquet, 2008). Umbach (2007) has also found that part-time instructors spend less time preparing for class and use less effective teaching practices as compared to tenure-track faculty.…”
Section: Discussionmentioning
confidence: 99%
“…As Kezar, Walpole, and Perna (2015) argue, institutions have not paid sufficient attention to the engagement of low-income and first-generation students, and they suggest strategies for meeting the needs of this population must focus on engagement in the classroom, instead of relying on activities outside the classroom. Given the trend of reliance on part-time contingent faculty, and the fact that they are essential to the success of students because of teaching the majority of courses, colleges should also pursue initiatives designed to forge part-time faculty connections to colleges and address labor conditions including part-time faculty compensation and opportunities for advancement (Bickerstaff & Chavarin, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Topics such as working with students who have learning disabilities, multiculturalism, inclusion, technology, time management, conflict resolution, etc. have all become common topics for these programs (Bickerstaff & Chavarin, 2018;Krug, 2018). The difficulty of offering such a broad range of development training is that it can become hard for faculty members to know how to prioritize a developmental agenda.…”
Section: Relevant Scholarshipmentioning
confidence: 99%